Dry Eye Disease following Refractive Surgery: A 12-Month Follow-Up of SMILE versus FS-LASIK in High Myopia. (15th November 2015) - Wang, Bingjie; Naidu, Rajeev K.; Chu, Renyuan; Dai, Jinhui; Qu, Xiaomei; Zhou, Hao
Abstract : Purpose. To compare dry eye disease following SMILE versus FS-LASIK. Design. Prospective, nonrandomised, observational study. Patients. 90 patients undergoing refractive surgery for myopia were included. 47 eyes underwent SMILE and 43 eyes underwent FS-LASIK. Methods. Evaluation of dry eye disease was conducted preoperatively and at 1, 3, 6, and 12 months postoperatively, using the Salisbury Eye Evaluation Questionnaire (SEEQ) and TBUT. Results. TBUT reduced following SMILE at 1 and 3 months (p < 0.001 ) and at 1, 3, and 6 months following FS-LASIK (p < 0.001 ). TBUT was greater following SMILE than FS-LASIK at 3, 6, and 12 months (p < 0.001, p < 0.001, andp = 0.009, resp.). SEEQ scores increased (greater symptoms) following SMILE at 1 month (p < 0.001 ) and 3 months (p = 0.003 ) and at 1, 3, and 6 months following FS-LASIK (p < 0.001 ). SMILE produced lower SEEQ scores (fewer symptoms) than FS-LASIK at 1, 3, and 6 months (p < 0.001 ). Conclusion. SMILE produces less dry eye disease than FS-LASIK at 6 months postoperatively but demonstrates similar degrees of dry eye disease at 12 months.